Board Effectiveness and Employee Engagement: Nigeria Stakeholder Perceptions (Issues in Social and Environmental Accounting (ISEA), 2013)
The objective of this study is to determine whether employee participation yields effective board performance. To stimulatedebates inthe stakeholder theoretical perspective in an attempt to offer more inclusive approach to strengthen the existing governance structure in Nigeria.This research intends to investigate the suitability of employees participating in board’s decision-making hierarchy because of their contractual importance as wealth creators of the firm. A conceptual model is proposed and tested on public listed companies in Nigeria based on survey perception of sampled 154 respondents. The study employs in-depth confirmatory factory analysis in a structural equation modeling approach. Building upon constructs such as union relations, productivity, and skilled-labor turnover, the study found the indicator variables measure employee participation, which focused more on the board’s control, operational decisions, and strategy in monitoring, service, and networking roles. Hence, we conclude that employees as important contractual company stakeholders affect board performance. Builds on the limited research agenda for boards and corporate governance that focus on coordinating, exploring and distribution of stakes using adventurous research designs and statistical tools, especially in Nigerian emerging economy. This paper exposes the firm’s potentials as provider of sustainable and longer-term benefits not only limited to equityholders, but also to employees as wealth creators, which will improve mutual trust, harmony and confidence for more stable and productive outputs that could give visibility to income inequality. The paper provides valid measures that link corporate governance debates to broader stakeholder perspective.